Nutrition and its footprints: Using environmental indicators to assess the nexus between sustainability and food - Hatjiathanassiadou, Maria; Rolim, Priscilla Moura; Seabra, Larissa Mont'Alverne Jucá (Frontiers in Sustainable Food Systems, 2023)
Nutrition science plays a key role in promoting sustainable diets, which is important to human and planetary health. Current food systems are associated with the unsustainable use of natural resources; therefore, rethinking current models is urgent and is part of a global agenda to reach sustainable development. Sustainable diets encompass health, society, economy, culture as well as the environment, in addition to considering all the stages that make up the food production chain. This study aimed to perform a review on the importance of using environmental footprints as a way of assessing the environmental impacts of food production and consumption and how they relate to human health and nutrition. The results show that environmental footprint has widely varying patterns of performance involving various indicators besides environmental, such as food waste, health, and food consumption indicators. Studies show that some dietary patterns such as high-ultra-processed foods increase the environmental impact. The use of carbon, water, and ecological footprint can improve indicator scores for food quality and consumption.